2017
DOI: 10.1200/jco.2017.73.5324
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Trial of Adjuvant Pazopanib Versus Placebo After Nephrectomy in Patients With Localized or Locally Advanced Renal Cell Carcinoma

Abstract: Purpose This phase III trial evaluated the efficacy and safety of pazopanib versus placebo in patients with locally advanced renal cell carcinoma (RCC) at high risk for relapse after nephrectomy. Patients and Methods A total of 1,538 patients with resected pT2 (high grade) or ≥ pT3, including N1, clear cell RCC were randomly assigned to pazopanib or placebo for 1 year; 403 patients received a starting dose of 800 mg or placebo. To address toxicity attrition, the 800-mg starting dose was lowered to 600 mg, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
204
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 338 publications
(226 citation statements)
references
References 20 publications
6
204
0
7
Order By: Relevance
“…The S-TRAC trial showed DFS benefit, without OS benefit [2]. The PROTECT trial failed to show DFS benefit, except for pazopanib 800mg subgroup, where accrual was interrupted due to adverse effects [3]. In all three reports, data have not reached adequate maturity for final…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The S-TRAC trial showed DFS benefit, without OS benefit [2]. The PROTECT trial failed to show DFS benefit, except for pazopanib 800mg subgroup, where accrual was interrupted due to adverse effects [3]. In all three reports, data have not reached adequate maturity for final…”
Section: Discussionmentioning
confidence: 98%
“…The search yielded seven prospective randomized trials of adjuvant targeted agents after nephrectomy for patients with high-risk nmRCC: ASSURE [1], S-TRAC [2], PROTECT [3], SORCE [6], EVEREST [7], ATLAS [8] and ARISER [9] (Table 1). The ARISER trial examined a carbonic anhydrase IX inhibitor (girentuximab).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Что касается обсуждаемого вопроса целесообраз-ности адъювантного лечения у больных раком почки высокого риска прогрессирования, перенесших нефр-эктомию, то несмотря на одобрение сунитиниба в ка-честве адъюванта Европейским агентством лекарст-венных средств, такое показание не вошло в рекомендации ЕAU в 2018 г. для сунитиниба, а также пазопаниба и сорафениба из-за спорного характера результатов в доступных исследованиях по адъювант-ной терапии [7][8][9].…”
Section: съезды и конференцииunclassified